The Lightning Arrester Modeling Using ATP-EMTP - Trin Saengsuwan,; Wichet Thipprasert, (Agriculture and Natural Resources, 2008)
This paper describes operating analysis of metal oxide surge arrester, IEEE Model, Pinceti Model and the new model proposed, using ATP-EMTP. Nowadays the utilities in Thailand such as the Provincial Electricity Authority (PEA) and the Metropolitan Electricity Authority (MEA) mostly use lightning arrester from Ohio Brass and Precise brands. The lightning arrester models are based on the Ohio Brass: PDV-100, 9 kV and Precise: Precise PAZ-A09_1 10 kA. Class 1, 30 kV. The tests are performed by applying standard impulse current wave (8/20). It is found that the models can predict the operation of the metal oxide surge arrester in the system with error of less than 1% at 10 kA. The percentages of error developed by the model using ATP-EMTP show that it can be use to predict or calculate energy consumption in each type of surge arresters. The percentage of error of this model is less than that of the other two models. From this reason, the result of prediction or estimation will be close to the real value of surge arrester in the normal condition of system.